A new genus and subgenus of Alysiini from China, with the description of two new species (Hymenoptera, Braconidae, Alysiinae) - Zhu, Jiachen; Achterberg, Cornelis Van; Chen, Xue-Xin (Zootaxa, 2017)
A new alysiine genus (Braconidae, Alysiinae, Alysiini) from SE China, Dacnulysia gen. nov. (type species: D. chaenomastax sp. nov.) with aberrant mandible and head shape is described and illustrated. A new species of the genus Phaenocarpa Foerster, 1863, with an aberrant ovipositor, P. platychora sp. nov., from SE China is included as type species in a new subgenus, Clistalysia nov. A key to the subgenera of Phaenocarpa Foerster is included; Idiolexis Foerster, 1863, and Kahlia Ashmead, 1900, are recognised as valid subgenera.